Gene targeting RhoA reveals its essential role in coordinating mitochondrial function and thymocyte development - Zhang, Shuangmin (J Immunol, 2014)
Thymocyte development is regulated by complex signaling pathways. How these signaling cascades are coordinated remains elusive. RhoA of the Rho family small GTPases plays an important role in actin cytoskeleton organization, cell adhesion, migration, proliferation, and survival. Nonetheless, the physiological function of RhoA in thymocyte development is not clear. By characterizing a conditional gene targeting mouse model bearing T cell deletion of RhoA, we show that RhoA critically regulates thymocyte development by coordinating multiple developmental events. RhoA gene disruption caused a strong developmental block at the pre-TCR checkpoint and during positive selection. Ablation of RhoA led to reduced DNA synthesis in CD4(−)CD8(−), CD4(+)CD8(−), and CD4(−)CD8(+) thymocytes but not in CD4(+)CD8(+) thymocytes. Instead, RhoA-deficient CD4(+)CD8(+) thymocytes showed an impaired mitosis. Furthermore, we found that abrogation of RhoA led to an increased apoptosis in all thymocyte subpopulations. Importantly, we show that the increased apoptosis was resulted from reduced pre-TCR expression and increased production of reactive oxygen species (ROS) which may be due to an enhanced mitochondrial function, as manifested by increased oxidative phosphorylation, glycolysis, mitochondrial membrane potential, and mitochondrial biogenesis in RhoA-deficient thymocytes. Restoration of pre-TCR expression or treatment of RhoA-deficient mice with a ROS scavenger NAC partially restored thymocyte development. These results suggest that RhoA is required for thymocyte development and indicate for the first time that fine-tuning of ROS production by RhoA, through a delicate control of metabolic circuit, may contribute to thymopoiesis.